Vibration energy and repeated-root modes of disc rotor for high-frequency brake squeal. (June 2019) - Gao, Pu; Du, Yongchang; Walker, Paul D
In this paper, the generation mechanism of high-frequency brake squeal is revealed from the perspective of vibration energy. Based on a closed-loop coupling model, vibration energy transfer paths at the friction coupling interface between brake pads and disc are derived. Vibration energy equilibrium analysis is used to verify the reliability and accuracy of the derivation and the presented result demonstrates that vibration energy transferred from disc rotor to pads is the dominant transfer path. It is also demonstrated that the disc rotor is the key substructure affecting high-frequency brake squeal. As the disc rotor is axisymmetric, its repeated-root modes may lead to unreasonable calculated results by using the substructure modal composition method for analyzing the brake squeal. In this study, these repeated-root modes are processed by using a modified substructure modal composition method to obtain one unique integrated substructure modal composition coefficient of each disc repeated-root modes. Finally, the presented method is applied to analyze the brake squeal in the 13 kHz frequency band. The results easily identify the key vibration modes of the disc affecting high-frequency brake squeal, verifying the reliability of the presented method.